Group Dynamics and Effective Communication: Strategies to Enhance Village Product Marketing in Deli Serdang Regency - Muhammad Yalzamul Insan; Erwansyah, Erwansyah (CV Raskha Media Group, 2025)
Village-owned products often struggle to penetrate broader markets due to limited marketing skills, weak group coordination, and suboptimal communication practices. This community engagement program aims to strengthen marketing capabilities among village groups in Deli Serdang Regency by enhancing group dynamics, improving interpersonal and digital communication skills, and promoting collaborative strategies. Using a participatory training model, focus group discussions, and hands-on mentoring, the program involved local producers, village officials, and community groups. The results indicate a significant improvement in group cohesiveness, role clarity, and communication flow, leading to better marketing initiatives, improved digital presence, and stronger product branding. This article discusses how structured group dynamics and effective communication can serve as critical levers for advancing rural marketing performance. The study highlights implications for sustainable community empowerment and provides recommendations for future community service programs.